The novel optical solitons with complex Ginzburg–Landau equation for parabolic nonlinear form using the ?6-model expansion approach - Isah, Muhammad Abubakar; yokus, Asif (Cambridge Scientific Publishers, 2023)
This work investigates the complex Ginzburg–Landau equation (CGLE) with parabolic law in nonlinear optics, this form of nonlinearity may also be seen in fiber optics. It is referred to as the fifth-order susceptibility, which is predominantly present in a transparent glass with intense femtosecond pulses at 620nmI. The ?6-model expansion approach is used to find dark, singular, periodic, and combined optical soliton solutions to the model. The results presented in this study are intended to improve the CGLE’s nonlinear dynamical characteristics. These solitons are significant resources in physics and telecommunications engineering. They led to several quick follow-up investigations. The hyperbolic sine, for example, appears in the calculation of the Roche limit and gravitational potential of a cylinder, while the hyperbolic cotangent appears in the Langevin function for magnetic polarization. Some of the obtained solutions’ 2-, 3-dimensional, and contour plots are shown. © CSP - Cambridge, UK; I&S - Florida, USA, 2023
Keywords: Jacobi elliptic functions; parabolic law nonlinearity; the complex Ginzburg–Landau equation; The ?6-model expansion method; traveling wave solution